2008
DOI: 10.1002/jsfa.3199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary humate supplementation to broilers on performance, slaughter, carcass and meat colour

Abstract: BACKGROUND: This experiment was designed to examine the effect of dietary humate supplementation primarily on pH and colour parameters of carcasses, breast fillets and drumsticks and, secondarily on performance and carcass characteristics in broilers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Therefore, one of the primary aims of the present study was to investigate the changes in colour characteristics (CIE L *, a * and b *) of pH, WHC and chemical compositions of both breast and thigh meats, and in blood metabolites and minerals as influenced by feeding with diets containing HS at different levels. The conducted colour evaluation of thigh and breast muscles of the chickens demonstrated that addition of HS to the diet may not only influence breeding effectiveness, but also the colour of their carcasses, as reported by Esenbuga et al 11 and Ozturk et al 10, 25 Despite augmentation in the L * value of thigh muscle from the supplement at 0.5 g kg −1 in comparison to the control, according to CIE lightness values of meats in poultry,33 the L * values for all treatments in the current study were not in a normal range and would be considered excessively pale. However since the redness (index) increased by HS, which are inherently brown to dark colour, it was possible to speak about colour darkening.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Therefore, one of the primary aims of the present study was to investigate the changes in colour characteristics (CIE L *, a * and b *) of pH, WHC and chemical compositions of both breast and thigh meats, and in blood metabolites and minerals as influenced by feeding with diets containing HS at different levels. The conducted colour evaluation of thigh and breast muscles of the chickens demonstrated that addition of HS to the diet may not only influence breeding effectiveness, but also the colour of their carcasses, as reported by Esenbuga et al 11 and Ozturk et al 10, 25 Despite augmentation in the L * value of thigh muscle from the supplement at 0.5 g kg −1 in comparison to the control, according to CIE lightness values of meats in poultry,33 the L * values for all treatments in the current study were not in a normal range and would be considered excessively pale. However since the redness (index) increased by HS, which are inherently brown to dark colour, it was possible to speak about colour darkening.…”
Section: Discussionmentioning
confidence: 54%
“…There is an increasing awareness that supplemental humic substance (HS) as a growth‐promoting agent has multiple health effects and nutritional benefits for domestic animals. This knowledge has resulted primarily from studies on the use of humic acids to improve the immune system of calves,1, 2 to treat digestive disorders and diarrhoea of cats and dogs3, 4 and on humates, including those in feed and water of poultry, to promote growth,5–9 carcass yield and characteristics,8–11 and egg production 12–15. These studies have, however, shown that the assumption that humates or HS might improve growth performance of poultry has not yet been confirmed, and thus a systematic approach to the efficacy and safety of compounds used as feed additives for poultry is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…These authors reported a greater effect on pH24 of the 10% humic-fatty acid preparation. Other studies performed on broilers have reported that HUS-supplemented diets actually lower meat pH (Aksu et al, 2005;Esenbuğa et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…However, studies show that both the recommended doses and estimated requirements of the hens are too high, and that the availability of inorganic compounds is insufficient (Esenbuga et al, 2008;Zhao et al, 2010). This is due to the limited absorption capacity of the gastrointestinal tract caused by the attachment of these micronutrients by various compounds (phytates, fiber fractions, and tannins).…”
Section: Introductionmentioning
confidence: 99%